TRANSFORMASI SISTEM PEMASARAN GLOBAL DI ERA DIGITAL - Elijon Tumanggor; Juwita Sihotang; Jesica Purba; Raymond Fransiscus (Jurnal Penelitian Progresif, 2025)
In the era of development, the digital age has had a considerable impact on the global marketing system. In this era, companies are required to be able to adapt to changes and developments in technology, consumer behavior, and international market dynamics that continue to grow rapidly. The use of social media, artificial intelligence, big data analytics and e-commerce platforms has transformed and influenced traditional marketing strategies to become more integrated, responsive, and data-driven. This article aims to find out how the global marketing system is transforming in the digital era, by prioritizing the strategies, challenges, and opportunities faced by companies in effectively reaching the global market